2014
DOI: 10.1055/s-0033-1361088
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Expressions in CD4+ and CD8+ T-cell Subsets in Autoimmune Thyroid Diseases

Abstract: tive expression 12,57 in HT vs. 19.40 in control group (CG), p = 0.0002; 12,10 in GD vs. 19.40 in CG, p = 0.0002) and in CD8 + -T-cells (13.13 in HT vs. 18,12 in CG, p = 0.02; 11.66 in GD vs. 18.12 in CG, p = 0.0002). GD and HT showed signifi cantly decreased miRNA 155_2 and miRNA 155*_1 in HT in CD8 + -T-cells (10.69 in HT vs. 11.30 in CG, p = 0.01; 10.40 in GD vs. 11.30 in CG, p = 0.005). This study confi rms signifi cant variations of miRNA200a and miRNA155 in patients suffering from GD and HT in vivo in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…The phenomenon that miRNA expression profile from peripheral blood is different from that of diseased tissue is also found in other diseases, such as IBD, RA, SLE and psoriasis [22,32,33,34,35,36,37,38]. In addition, our results are also different from study done by Bernecker et al, in which they confirmed significant variations of miR-200a and miR-155 in CD4+ T-cells and CD8+ T-cells from AITD patients [39]. The reason for this divergence not only due to the different materials but also the different methods.…”
Section: Discussioncontrasting
confidence: 99%
“…The phenomenon that miRNA expression profile from peripheral blood is different from that of diseased tissue is also found in other diseases, such as IBD, RA, SLE and psoriasis [22,32,33,34,35,36,37,38]. In addition, our results are also different from study done by Bernecker et al, in which they confirmed significant variations of miR-200a and miR-155 in CD4+ T-cells and CD8+ T-cells from AITD patients [39]. The reason for this divergence not only due to the different materials but also the different methods.…”
Section: Discussioncontrasting
confidence: 99%
“…GD and HT patients had significantly lower levels of miR-146a-5p and miR-155-5p in the thyroid tissues, respectively (128). A subsequent study by Bernecker et al found that GD and HT patients had lower level of miR-155-5p in HT in CD8+ T cells than controls (130). Wei et al reported that Graves’ ophthalmopathy patients had significantly lower levels of miR-146a-5p than controls, and miR-146a-5p was negatively correlated with serum level of IL-17, which had been suggested to be an important pathogenic cytokine in the development of Graves’ ophthalmopathy (33, 34, 137).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…For example, it was observed that the expression of miR-154*, miR-376b, and miR-431* was suppressed in PBMC from initial GD patients with respect to healthy controls, but recovered in GD patients in remission (39). Others observed that serum levels of miR-22, miR-375, and miR-451 were increased in patients with HT compared with healthy subjects and that serum levels of miR-16, miR-22, miR-375, and miR-451 were increased in patients with GD (40), while another study revealed significant variations of miR-200a and miR-155 in purified CD4+ T-cells and CD8+ T-cells of patients suffering from GD and HT (41). More recent studies attempted to explain the biological significance of miRNA deregulation or their possible clinical implications in AITD (4246).…”
Section: Non-coding Rnas In Aitdmentioning
confidence: 99%